Distinctions of a learning content for education in the field of nanotechnology. (2017) - Shakhnov, V.A.; Zinchenko, L.A.; Rezchikova, E.V.; Verstov, V.A.
The possibility of using non-traditional methods of transmitting knowledge, such as structurally-logic schemes, dynamic content, and the theory of solving inventive problems is considered along with the classic methods for studying the characteristics of nanotechnology.